PENGARUH PENGGUNAAN ANALISIS FUNDAMENTAL DAN OVERCONFIDENCE TERHADAP PENGAMBILAN KEPUTUSAN INVESTASI PADA INVESTOR MILENIAL DI BLITAR - Iwan Setya Putra; Thesa Elisabet (Pusat Penelitian dan Pengabdian bagi Masyarakat Politeknik Negeri Tanah Laut, 2022)
The purpose of this study is to determine the effect of fundamental analysis and overconfidence behavior in investment decisions for millennial investors in Blitar. This study uses quantitative research with data collection techniques through questionnaires distributed to investors in the Blitar area. Using the purposive sampling technique, the sample taken in this study was 73 millennial investors in Blitar. Method of analysis using classical assumption test, multiple linear regression analysis, and hypothesis testing. The results of this study indicate that fundamental analysis has no significant effect on investment decision making for millennial investors in Blitar, overconfidence has a significant effect on investment decision making on millennial investors in Blitar, and simultaneously fundamental analysis and ovce have a significant effect on investment decision making on millennial investors in Blitar.erconfiden